Implementasi Kebijakan Tarif Layanan Parkir di Kota Pekanbaru - Vena Dunya; Mimin Sundari Nasution (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2024)
The Pekanbaru City Government has officially increased motor vehicle parking rates on the edge of public roads since the issuance of Pekanbaru Mayor Regulation Number 41 of 2022 concerning Parking Service Rates. This step was taken not only to increase Local Original Income, but also aimed to control mobility and the use of private vehicles to reduce congestion. This research was motivated by the lack of improvement in the quality of parking services after the tariff increase, including parking attendants who did not serve according to SOPs, the absence of parking signs and markings in some locations, and public rejection of parking attendants in small shops and neighborhood roads. The purpose of the study was to analyze the implementation of parking service tariff policies in Pekanbaru City. The research method used is a qualitative method with data collection techniques through observation, interviews and documentation. The results showed that the implementation of the regulation has not been optimal, caused by obstacles such as uneven socialization to parking attendants, supervision and delivery of information that is not optimal, infrastructure improvements that hinder the provision of parking signs and markings, and community non-compliance with parking operations.